2022
DOI: 10.21203/rs.3.rs-2083312/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of the TRIM24 bromodomain reactivates latent HIV-1

Abstract: Expression of the HIV-1 genome by RNA Polymerase II is regulated at multiple steps, as are most cellular genes, including recruitment of general transcription factors and control of transcriptional elongation from the core promoter. We discovered that tripartite motif protein TRIM24 is recruited to the HIV-1 Long Terminal Repeat (LTR) by interaction with TFII-I and causes transcriptional elongation by stimulating association of PTEF-b/ CDK9. Because TRIM24 is required for stimulation of transcription from the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…10C, PMA, PEP005). In contrast we found that treatment of RBH infected CDK8 KO cells with the histone deacetylase inhibitor SAHA, or the bromodomain inhibitors JQ1 and IACS-957 18 failed to recapitulate the level of productive infections observed for wildtype cells (Fig. 10C, SAHA, JQ1, IACS-9571).…”
Section: Cdk8 and Cdk19 Are Activators Of Hiv-1 Expression The Result...mentioning
confidence: 69%
“…10C, PMA, PEP005). In contrast we found that treatment of RBH infected CDK8 KO cells with the histone deacetylase inhibitor SAHA, or the bromodomain inhibitors JQ1 and IACS-957 18 failed to recapitulate the level of productive infections observed for wildtype cells (Fig. 10C, SAHA, JQ1, IACS-9571).…”
Section: Cdk8 and Cdk19 Are Activators Of Hiv-1 Expression The Result...mentioning
confidence: 69%
“…To examine specific effects of USF1 and USF2 on HIV-1 expression we produced USF1 and USF2 gene knockouts (KO) (Fig. 1A, 1B) in the Jurkat Tat mHIV-Luc T cell line bearing an integrated HIV-1 mini-virus where luciferase expression is driven by the 5' LTR (Bernhard et al 2011) (Horvath, Brumme, and Sadowski 2023). Surprisingly, we noted that USF1 protein abundance was reduced in all USF2 knockout lines (Fig.…”
Section: Regulation Of Hiv-1 Expression By Usf1 and Usf2 Previous Stu...mentioning
confidence: 92%
“…Next, we examined effect of the USFs on reactivation in response to the bromodomain inhibitors JQ1 and IACS-9571. JQ1 is a well-studied LRA that inhibits the BRD4 bromodomain causing increased Tat transactivation (Li et al 2013), while IACS-9571 inhibits the TRIM24 bromodomain causing increased LTR occupancy of this factor and stimulation of transcriptional elongation Horvath, Brumme, and Sadowski 2023) .…”
Section: Effect Of Usf1 and 2 On Response Of Hiv-1 To Latency Reversi...mentioning
confidence: 99%
See 2 more Smart Citations